Developing English for Front Office Learning Materials - Wibawa, I Gusti Putu Satria; Wedanthi, Nyoman Karina; Dewi, Kadek Sintya; Budasi, I Gede (STKIP AGAMA HINDU SINGARAJA, 2021)
This study aims to develop English language materials of front office for second semester students of the eleventh grade at SMK N 2 Singaraja. This study adopts the Design and Development (D&D) which is guided by data collection through six instruments, namely questionnaires for teacher and front office staff, Google form for teachers and students, checklist for students, and checklist for expert judges. There are three stages that the researcher takes to complete this study, namely designing, developing, and evaluating the quality of the teaching materials (product) so that it can be categorized as a good material. The result is that there are four topics developed by the researcher, namely (1) Renewal of reservations, (2) Cancellation of reservations, (3) Handling of group reservations orally and in writing, and (4) Handling of individual reservations orally and in writing.